Social cues drive the evolution of plastic pathogen virulence in spatially and temporally variable environments - Ryuichi Kumata; Sébastien Lion; Edze R. Westra; Sylvain Gandon (Proceedings of the National Academy of Sciences, 2026)
Host–pathogen interactions are often characterized by spatial and temporal fluctuations in host density. Such variability may promote the evolution of phenotypic plasticity in pathogen virulence. However, it remains unclear how pathogens can reliably detect changes in host density. Here we show that some pathogens may exploit social cues, such as the presence of infected hosts, to gain indirect information about transmission opportunities when the density of susceptible hosts fluctuates. Our analysis demonstrates that virulence plasticity does not evolve in constant environments, but temporal and spatial variability can promote the evolution of reduced virulence in pathogens capable of detecting infected hosts. Selection for plasticity arises from the covariance between social cues and the availability of susceptible hosts. We compare the effects of temporal variation and spatial structure on the evolution of plasticity and clarify the ecological conditions under which communication systems based on social cues can emerge among viruses and other microbes. More broadly, this work provides a theoretical framework for understanding the adaptive value of plastic life-history strategies in pathogens facing variable environments.